Testimonium De Auditu in The Case Rape of Childrens - Citra Dewi Keumala; Rizanizarli Rizanizarli; Syarifuddin Hasyim (Universitas Islam Negeri Antasari Banjarmasin, 2022)
A judge can impose a sentence on a person, if the judge has at least two valid pieces of evidence as stated in Article 183 of the Criminal Procedure Code. However, in handling cases of child sexual abuse, most of the witnesses presented in the trial include hearsay evidence or it can be called as a testimony obtained from other people.This study aimed to determine the strength of a hearsay evidence given by a witness in a crime of child sexual abuse and to explain the judge’s consideration regarding the hearsay evidence in imposing a sentence of child sexual abuse crime The data of this study were obtained through a literature review and an interview with the informants. The research found that the strength of a hearsay evidence was stated in the Constitutional Court Decision Number 65/PUU-VIII/2010 in this criminal trial as a real effort to protect the rights of the suspects and defendants. In addition, the judge's consideration regarding the hearsay evidence could be seen by the fact that the evidence was not completely rejected by the judge. Although the testimony given by the witness was not valid as a evidence, it was useful as a guide in handling the case. Therefore, it is recommended to develop the results of the Constitutional Court Decision Number 65/PUU-VIII/2010 regarding the hearsay evidence that can be used by judges and qualified as a free evidence (vrij bewijskracht). Hakim dapat menjatuhkan pidana kepada seseorang, jika hakim sekurang-kurangnya memiliki dua alat bukti yang sah terdapat dalam KUHAP Pasal 183. Namun dalam penanganan perkara jarimah pemerkosaan terhadap anak, sebagian besar saksi yang dihadirkan dalam persidangan termasuk Testimonium De Auditu atau dapat disebut keterangan yang diperoleh dari orang lain”.“Penelitian ini bertujuan untuk menjelaskan kekuatan pembuktian kesaksian Testimonium De Auditu dalam Jarimah pemerkosaan terhadap anak dan menjelaskan pertimbangan hakim atas kesaksian Testimonium De Auditu dalam memutuskan Jarimah pemerkosaan terhadap anak. Data yang terdapat dalam penelitian ini melalui peninjauan kepustakaan serta wawancara narasumber. Metode yang digunakan dalam penelitian ini adalah yuridis normatif, Dapat disimpulkan bahwa hasil penelitian mengenai kekuatan testimonium de auditu diakui dalam Putusan Mahkamah Konstitusi Nomor 65/PUU-VIII/2010 dalam peradilan pidana ini sebagai upaya nyata perlindungan terhadap hak-hak tersangka dan terdakwa, serta pertimbangan hakim menggunakan kesaksian Testimonium de auditu tidak sepenuhnya ditolak hakim,meskipun kesaksian yang diberikan oleh saksi tersebut tidak bernilai sebagai alat bukti melainkan sebagai petunjuk dalam memutuskan sebuah perkara. Maka disarankan untuk dilakukannya pengembangan atas hasil Putusan Mahkamah Konstitusi Nomor 65/PUU-VIII/2010 mengenai testimonium de auditu tersebut dapat digunakan oleh hakim namun kembali lagi kekuatan alat bukti persangkaan hakim ini pada dasarnya adalah bebas (vrij bewijskracht).